Facile synthesis and optimization of nickel oxide nanoparticles using Polianthes tuberosa extract and its anticancer activity - Sundaram, Kaveri; Mohanrao, Santhosh Kumar (Journal of Phytology, 2022)
NiO nanoparticle has been synthesized by a greener method using Polianthes tuberosa plant extract. The nanoparticle was characterized by UV-Visible, FT-IR, XRD and SEM instrumental techniques. The absorption band appeared at 269 nm in UV-Visible spectrum supported the formation of NiO nanoparticles. The IR spectrum analysis showed a broad band at 554 cm-1 characteristics of NiO nanoparticles. From the XRD results, the crystalline size and shape of NiO nanoparticles was determined to be 3.23 nm with a face centered cubic crystal. The NiO nanoparticles has been distributed well. From SEM results, the synthesized NiO sample has particle size between 5 and 11 nm range. The cytotoxic results showed significant activity of the synthesized NiO nanoparticles against MM2 and HeLa cells.